Photocatalytic metal-organic framework from cds quantum dot incubated luminescent metallohydrogel - Saha, Subhadeep; Das, Gobinda; Thote, Jayshri; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Cadmium sulfide (CdS) quantum dots (<10 nm in size) have been successfully synthesized in situ without any capping agent in a Zn(II)-based low-molecular-weight metallohydrogel (ZAVA). Pristine ZAVA hydrogel shows blue luminescence, but the emission can be tuned upon encapsulation of the CdS quantum dots. Time-dependent tunable emission (white to yellow to orange) of the CdS incubated gel (CdS@ZAVA gel) can be attributed to sluggish growth of the quantum dots inside the gel matrix. Once CdS quantum dots are entrapped, their augmentation can be stopped by converting the gel into xerogel, wherein the quantum dots remains embedded in the solid xerogel matrix. Similar size stabilization of CdS quantum dots can be achieved by means of a unique room-temperature conversion of the CdS incubated ZAVA gel to CdS incubated MOF (CdS@ZAVCl) crystals. This in turn arrests the tunability in emission owing to the restriction in the growth of CdS quantum dots inside xerogel and MOF. These CdS embedded MOFs have been utilized as a catalyst for water splitting under visible light.

Photoluminescent tetrahedral d(10)-metal Schiff base complexes exhibiting highly ordered mesomorphism - Chakraborty, Sutapa; Purkayastha, Debraj Dhar; Das, Gobinda; Bhattacharjee, Chira R.; Mondal, Paritosh; Prasad, S. Krishna; Rao, D. S. Shankar (Polyhedron, 2016)
A series of four-coordinate d(10)-metal complexes of the type [ML2] {M = Zn, Cd, Hg; L = 4-nitro-2-((octadecylimino)methyl)phenol}, incorporating a new N-alkylated bidentate [N,O]-donor salicylaldimine Schiff base ligand, has been synthesized and characterized by elemental analyses, FT-IR, UV-Vis, H-1 NMR and FAB-mass spectroscopies. The ligand is non-mesomorphic and devoid of any photoluminescence. The zinc(II) and cadmium(II) complexes displayed highly ordered mesophases reminiscent of soft crystals. The phases have been characterized by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) studies. The complex of mercury(II) decomposed prior to melting. An orthogonal symmetry with a `herringbone' array for the zinc complex and a primitive triclinic symmetry (p(1)) for the cadmium complex, respectively, has been proposed. The complexes exhibited fluorescence at room temperature, both in the solution and in the solid state, with emission maxima in the blue region. Density functional theory (DFT) calculations carried out using the GAUSSIAN 09 program at the B3LYP level revealed a distorted tetrahedral geometry around the metal center in all the complexes. Natural bond orbital (NBO) analysis suggested appreciable charge transfer from the ligand to the metal center in the complexes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Density functional theory; Luminescence; Mesophase; Schiff base; X-ray diffraction